Household solid waste management: how effective are the strategies used in Harare Zimbabwe? - Mandevere, B; Jerie, Steven (Allied Academies, 2022)
Sustainable development accompanied by a clean environment is desirable although many urban councils in developing countries have persistently failed to achieve this. The City of Harare authorities are ceased with the status of household solid waste management service delivery. This study therefore aimed to investigate the effectiveness of the strategies employed by the City of Harare in household solid waste management. To achieve this, structured questionnaires, interviews, observations and focus group discussions were employed in data gathering together with secondary data. The study was conducted in Harare’s low, medium and high-density income suburbs. Findings revealed that organic solid waste constituted the largest proportion of waste generated in Harare and other forms are also generated yet their collection is very minimal. Residents resort to illegal night dumping, resulting in the proliferation of associated diseases. In light of these findings, it was recommended that waste collection entities be capacitated, people be educated on waste recycling, reduction and reusing. A commission be put in place to ensure proper enforcement of waste legislation, effective and sustainable day in running of household solid waste management in the city.